Adsorptive removal of naproxen from water using polyhedral oligomeric silesquioxane (POSS) covalent organic frameworks (COFs) - Bala, Suleiman; Che Abdullah, Che Azurahanim; Mohamed Tahir, Mohamed Ibrahim; Abdul Rahman, Mohd Basyaruddin (Multidisciplinary Digital Publishing Institute, 2022)
Covalent organic frameworks are porous crystalline compounds made up of organic material bonded together by strong reversible covalent bonds (these are novel types of materials which have the processability of extended or repeated structures with high performance, like those of thermosets and thermoplastics that produce high surface coverage). These have a long-term effect on an arrangement’s geometry and permeability. These compounds are entirely made up of light elements like H, B, C, N, O and Si. Pharmaceuticals and personal care products (PPCPs) have emerged as a new threatened species. A hazardous substance known as an “emerging toxin,” such as naproxen, is one that has been established or is generated in sufficient amounts in an environment, creating permanent damage to organisms. COF-S7, OAPS and 2-methylanthraquionone(2-MeAQ), and COF-S12, OAPS and terephthalaldehyde (TPA) were effectively synthesized by condensation (solvothermal) via a Schiff base reaction (R1R2C=NR′), with a molar ratio of 1:8 for OAPS to linker (L1 and L2), at a temperature of 125 °C and 100 °C for COF-S7 and COF-S12, respectively. The compounds obtained were assessed using several spectroscopy techniques, which revealed azomethine C=N bonds, aromatic carbon environments via solid 13C and 29Si NMR, the morphological structure and porosity, and the thermostability of these materials. The remedied effluent was investigated, and a substantial execution was noted in the removal ability of the naproxen over synthesized materials, such as 70% and 86% at a contact time of 210 min and 270 min, respectively, at a constant dose of 0.05 g and pH 7. The maximum adsorption abilities of the substances were found to be 35 mg/g and 42 mg/g. The pH result implies that there is stable exclusion with a rise in pH to 9. At pH 9, the drop significance was attained for COF-S7 with the exception of COF-S12, which was detected at pH 11, due to the negative Foster charge, consequent to the repulsion among the synthesized COFs and naproxen solution. From the isotherms acquired (Langmuir and Freundlich), the substances displayed a higher value (close to 1) of correlation coefficient (R2), which showed that the substances fit into the Freundlich isotherm (heterogenous process), and the value of heterogeneity process (n) achieved (less than 1) specifies that the adsorption is a chemical process. Analysis of the as-prepared composites revealed remarkable reusability in the elimination of naproxen by adsorption. Due to its convenience of synthesis, significant adsorption effectiveness, and remarkable reusability, the as-synthesized COFs are expected to be able to be used as potential adsorbents for eliminating AIDs from water.